ДЕРЖАВНА ПОЛІТИКА УКРАЇНІЗАЦІЇ СИСТЕМИ ОСВІТИ УКРАЇНСЬКИХ УРЯДІВ У ДОБУ НАЦІОНАЛЬНОЇ РЕВОЛЮЦІЇ (1917-1920 рр.) - Kupriychuk, Vasyl; Khmelivska, Svitlana; Ilyin, Igor; Pinkevich, Vladyslav (Zhytomyr Ivan Franko State University, 2024)
The article provides a detailed analysis of the implementation of the state policy of education system’s Ukrainization in the course of the activities of Ukrainian governments (the Ukrainian Central Council, the Ukrainian State of the Hetmanate of Pavlo Skoropadskyi, the Directory of the Ukrainian People's Republic) and their influence on the development of the Ukrainian state formation in 1917-1920. The authors analyze a whole galaxy of congresses – (the First All-Ukrainian Teachers' Congress (April 1917), the First All-Ukrainian Peasants' Congress at the beginning of June 1917, the Second All-Ukrainian Teachers' Congress (August 1917)) that determined the position of educators regarding prospects and development of national education in the conditions of revolutionary restructuring of society. The desire of Ukrainian governments to create more opportunities to acquire education in their native language in the national educational institution is highlighted, which was the impetus for the opening of the Ukrainian National University in October 1917 as part of the historical-philological, physical-mathematical and of law faculties. Later similar educational institutions were opened in Mykolaiv, Kharkiv, Odesa. Projects of national universities were developed in Kamianets-Podilskyi and Uman. Also, departments of the Ukrainian language were founded in Kharkiv and Odesa ("classical") universities and four departments of Ukrainian studies - language, literature, history and law at the University of St. Volodymyr. In November 1917 the Ukrainian Scientific and Pedagogical Academy was opened, which became the first national higher educational institution in Ukraine. The state-building policy of Ukrainization of the education system of the government of the Ukrainian Central Rada, which was continued by the government of the Ukrainian State of Hetman P. Skoropadsky, was outlined, which made it possible to create more than 150 Ukrainian gymnasiums. A wide network of general cultural institutions and institutions was founded. In the past, Russian universities in Kyiv, Odesa, Kharkiv, as well as Katerynoslav Mining, Kharkiv Technological and Veterinary and Kyiv Polytechnic Institutes were nationalized and declared Ukrainian. Also, new departments in Ukrainian philology, history, culture, and Western Russian law were opened in scientific institutions, in addition to the existing ones. Kyiv National University was also reformed, turning it into a state. A law was adopted on the establishment of a Ukrainian university in Kamianets-Podilskyi with the prospect of developing higher humanities in Podillia and Western Ukraine and establishing scientific ties with universities in Western Europe.